Case Report: Successful Mechanical Thrombectomy in a Newborn With Basilar Artery Occlusion - Stracke, Christian Paul; Meyer, Lukas; Schwindt, Wolfram; Ranft, Alexander; Straeter, Ronald (Frontiers in Neurology, 2022)
Background: Neonatal stroke remains a rare condition that has not yet been approached in the field of endovascular treatment. Case: We present the first case report of a successful mechanical thrombectomy in a newborn basilar occlusion 14 hours after birth. Complete reperfusion of the basilar artery was achieved after two thrombectomy maneuvers with stent retrievers. Imaging follow-up proved patency of the target vessel and at day 30 the patient showed no neurologic deficits. Conclusions: Mechanical thrombectomy appears to be a feasible method to treat stroke in neonates with proximal cerebral artery occlusions.